(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
For the Gerdjikov-Ivanov equation, by using the method of dynamical system, this paper investigates the exact explicit solutions with the form q(x, t) = φ(ξ) exp [i(κ x-ω t +θ(ξ)],ξ= x-ct. In the given parameter regions, more than 14 explicit exact parametric representations are presented.